PENERAPAN METODE PROYEK PADA POKOK BAHASAN MOMENTUM DAN IMPULS UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN PENGUASAAN KONSEP SISWA SMA - Agusta, Rosa Nika (2014)
The study of physics at school is not only for preparing the students be ready to continue in college, but also for preparing the students to solve the problems, make decisions, think and act scientifically based on the concepts of science which have been taught. All of those have purpose to realize our nation goals such as have good society, have qualified and competent people like having the ability of critical thinking and problem solving, based on national education purpose in XXI and it has been agreed by BSNP 2010. The purpose of this research is to know the students' improvement in their concept mastery and critical thinking after applying the project method in studying physics for the material of momentum and impuls. The design of this research is one group pretest-posttest design. The research sample is the eleventh grade students of state senior high school in Bandung which has been chosen by using purposive sampling technique. Technique of collecting the data by using test instrument of concept mastery and critical thinking skill. The results of this research show that there is an improvement in students' concept mastery and critical thinking skill. It can be seen from the gain of the students' concept mastery which is normalized 0.325 and the category is average, and the gain of students' critical thinking which is normalized 0.302 and the category is average.